Pengaruh Dana Desa dan Alokasi Dana Desa terhadap tingkat kemiskinan dikabupaten Bogor - Arunia Trie Wulansari; Arunia; Amyulianthy, Rafrini; Herlan (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2024)
This research has achievements in order to test the role of village funds and village fund allocation in poverty levels in Bogor district in 2022. This research applies procedures based on data processing and the type of data used, namely complementary data obtained through the Community and Village Empowerment Service (DPMD ) Bogor district. The results collected were then studied applying classical assumption tests as well as multiple linear regression studies on village funds and village fund allocation as independent variables and poverty level as the dependent variable. The results of this research indicate that based on simultaneous (F test) village funds and village fund allocations have a good role in the poverty level of Bogor Regency, based on partial (t test) village funds and village fund allocations have a significant effect on the poverty level of Bogor Regency. This economic view has not been implemented in accordance with the regulations established and created because individual interests and preferences conflict with each other. This is in accordance with the theory used, namely Public Choice Theory.